PENINGKATAN PARTISIPASI PEMILIH MILENIAL: STRATEGI KOMUNIKASI DAN SOSIALISASI KOMISI PEMILIHAN UMUM PADA PEMILU 2019 - Dila, Novita; Fitri, Ai (Fakultas Komunikasi, Sastra, dan Bahasa, 2020)
In the era of the Industrial Revolution 4.0, the General Election Commission (KPU) does not only utilize conventional media, but also new media as part of the communication and socialization strategy in the 2019 General Election, one of the targets was the millennial generation, especially 17-year-olds who were first used their voting rights. This study aims: 1) to analyze the communication and socialization strategies of the General Election Commission in increasing millennial voter participation in Bekasi City, 2) Evaluating the level of millennial voter participation, and 3) Analyzing several factors that cause an increase in millennial voter participation. This study applied a qualitative method with a case study research design. Data obtained through direct observation, in-depth interviews, and documentation. The informants in this study were the Commissioner of the General Election Commission of Bekasi City, Political Party Officer, and Millennial Voters. The selection of informants in this study was determined based on purposive sampling and snowball sampling techniques. Data analysis techniques used include: 1) data collection, 2) data reduction, 3) data presentation, and 4) draw conclusions or verification. The research location was conducted at the General Election Commission of Bekasi City. The research findings show that the strategy carried out by the General Election Commission in increasing the participation of Millennial Voters in Bekasi City uses dialogical methods and communicating directly with voters, this has an impact on increasing Millennial Voter Participation in the 2019 General Election, besides that, several other supporting factors are political awareness. Society, especially Millennial Voters, is getting better and political education is also more effective.